Performance benchmarking of new software stream ciphers for secure multimedia streaming in resource-constrained devices - Sarcaoga, Ronald L. (2010)
Multimedia streaming on resource-constrained devices have become popular recently due to the introduction of mobile devices that are able to connect to the Internet using conventional wireless access points. Secure streaming, however, remains a challenge for these constrained devices due to their limited processing power and memory capacity. Thus for confidential transfer of multimedia content, there is a need for efficient and innovative algorithms that reduce the encryption footprint during actual streaming and playback. This research evaluated the performance of modern stream ciphers for use in secure video streaming using WLAN-enabled devices such as mobile phones and netbooks. Results show that software stream ciphers belonging to the final eSTREAM portfolio outperform AES by several metrics. Moreover, a selective encryption scheme was used to further enhance encryption efficiency. By using such scheme, the mediocre streaming experience brought about by a memory-optimized implementations of AES was significantly improved.